DIETARY MANAGEMENTOF POLLUTION GENERATED EPIDEMICS AS A RESULT OFNATURAL DISASTERS - Joshi, Monica (International Journal of Research -GRANTHAALAYAH, 2015)
Natural disasters at times are themselves the result of uncontrolled exploitation of natural resources. Deforestation results in soil erosion, in the initial stage and if uncontrolled, in the ultimate analysis, is found to be the basic reason for landslides and such other catastrophic disasters. It can thus be seen that the excessive exploitation of natural resources, without any program for restoration and replenishment of the damage done leads to an ecological imbalance that the generations to come have to live with. Besides there being an irreparable damage to the flora and fauna, the natural resources shall become a matter to be read about in journals and historical articles.